Combined Impact of Salt Precipitation and Fines Migration on CO2 Injectivity Impairment - Md Yusof, M.A. (Elsevier Ltd, 2021)
Reactive fluid/rock interactions during carbon dioxide (CO2) injection into saline aquifers would trigger injectivity issues, particularly due to the presence of salt precipitation and fines migration. Previous CO2 injectivity change models, on the other hand, are ascribed by permeability change caused by salt precipitation without taking into account the alteration caused by fines migration. Therefore, this research aims to develop a correlation to predict the CO2 injectivity in which the permeability change is described as a function of brine salinity, CO2 injection flow rate, particle size and particle concentration parameters. The impacts of individual and combined interactions between these parameters were investigated using core flooding experiments. The experiments were performed using Berea sandstone saturated with different brine salinities between 0 and 100,000 ppm. Then, CO2 saturated brine which contains various concentrations of different-sized particles was injected followed by several supercritical CO2 (scCO2) injection from 2 to 10 cm3/min. The percentage difference between the initial and final permeabilities was used to calculate the permeability change. Lastly, the statistical response surface methodology (RSM) was applied to model and predict the permeability changes. The relationship between permeability change and the interaction effects of four design parameters were explained with the help of 2D response surface using analysis of variance (ANOVA). The experimental results showed that brine salinity has a greater influence on permeability reduction as compared to the particles and CO2 injection flow rates. The presence of both salt precipitation and fines migration during scCO2 injection was found to intensify the permeability reduction up to threefold with increasing brine salinity and particle size. The newly developed model fit well with the experimental data and was statistically validated with reported data from different case studies. Â© 2021 Elsevier Ltd